Computer Exhumation in the Daniel Moyano Virtual Archive. A Reflection about Writing Formats, Materiality and the Evolution of Originals and Drafts - Vigna, Diego (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This paper addresses central notions concerning writer’s archives, based on an experiment conducted in the Daniel Moyano Virtual Archive: the recovery of texts from an outdated computing device. These texts were preserved by Moyano in a storage media inaccessible for present times, and were recovered in a joint effort between the CRLA-Archives (France) and the National University of Cordoba (Argentina). From a hermeneutical perspective, computer exhumation of these documents allowed us to articulate the genesis of the author ́s processes of fictionalization -not restricted to texts considered literary at first glance- with a socio-technical interrogation about these practices. This has inspired questions about the transformation of role of technique, particularly in the relation between art and society